Mouse model of severe recessive RYR1-related myopathy. (20th May 2019) - Brennan, Stephanie; Garcia-Castañeda, Maricela; Michelucci, Antonio; Sabha, Nesrin; Malik, Sundeep; Groom, Linda; Wei LaPierre, Lan; Dowling, James J; Dirksen, Robert T
Abstract: Ryanodine receptor type I (RYR1)-related myopathies (RYR1 RM) are a clinically and histopathologically heterogeneous group of conditions that represent the most common subtype of childhood onset non-dystrophic muscle disorders. There are no treatments for this severe group of diseases. A major barrier to therapy development is the lack of an animal model that mirrors the clinical severity of pediatric cases of the disease. To address this, we used CRISPR/Cas9 gene editing to generate a novel recessive mouse model of RYR1 RM. This mouse ( Ryr1 TM/Indel ) possesses a patient-relevant point mutation (T4706M) engineered into 1 allele and a 16 base pair frameshift deletion engineered into the second allele. Ryr1 TM/Indel mice exhibit an overt phenotype beginning at 14 days of age that consists of reduced body/muscle mass and myofibre hypotrophy. Ryr1 TM/Indel mice become progressively inactive from that point onward and die at a median age of 42 days. Histopathological assessment shows myofibre hypotrophy, increased central nuclei and decreased triad number but no clear evidence of metabolic cores. Biochemical analysis reveals a marked decrease in RYR1 protein levels (20% of normal) as compared to only a 50% decrease in transcript. Functional studies at end stage show significantly reduced electrically evoked Ca 2+ release and force production. In summary, Ryr1 TM/Indel mice exhibit a post-natal lethal recessive form of RYR1 RM that pheno-copies the severe congenital clinical presentation seen in a subgroup of RYR1 RM children. Thus, Ryr1 TM/Indel mice represent a powerful model for both establishing the pathomechanisms of recessive RYR1 RM and pre-clinical testing of therapies for efficacy.